2010
DOI: 10.1016/j.marpolbul.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Tracing sewage and natural freshwater input in a Northwest Mediterranean bay: Evidence obtained from isotopic ratios in marine organisms

Abstract: Elemental carbon and nitrogen levels and isotope ratios were assessed in different biological compartments of a Northwest (NW) Mediterranean bay to trace the various sources of nutrient input from natural (river runoffs) and anthropogenic (harbor outflows, fish farms and urban sewage outfall) sources. Samples from transplanted mussels and natural sea grass communities (Posidonia oceanica leaves and epiphytes) were harvested from different locations throughout the bay during the touristic summer and rainy seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Surprisingly, in Revellata Bay, the Δ 15 N values between impacted and control sites were far higher and also more consistent compared to those previously measured in other Mediterranean coastal open water and non-estuarine areas (Vizzini & Mazzola 2006, Lassauque et al 2010. In fact, our Δ 15 N ranges for gastropods at Revellata Bay fell within those reported from areas receiving high nitrogen loads in Mediterranean lagoons (Carlier et al 2008) and worldwide, in both freshwater and marine systems (Cabana & Rasmussen 1996, Riera et al 2000, McKinney et al 2001, Tewfik et al 2005 (Table 7).…”
Section: Indicators Of Anthropogenically Derived Nutrientssupporting
confidence: 82%
“…Surprisingly, in Revellata Bay, the Δ 15 N values between impacted and control sites were far higher and also more consistent compared to those previously measured in other Mediterranean coastal open water and non-estuarine areas (Vizzini & Mazzola 2006, Lassauque et al 2010. In fact, our Δ 15 N ranges for gastropods at Revellata Bay fell within those reported from areas receiving high nitrogen loads in Mediterranean lagoons (Carlier et al 2008) and worldwide, in both freshwater and marine systems (Cabana & Rasmussen 1996, Riera et al 2000, McKinney et al 2001, Tewfik et al 2005 (Table 7).…”
Section: Indicators Of Anthropogenically Derived Nutrientssupporting
confidence: 82%
“…As previously stated, δ 15 N values are commonly considered as an effective proxy of anthropic contamination. In the NW Mediterranean, δ 15 N values measured for P. oceanica range between 2 ‰ in rather pristine sites to 7 ‰ in polluted sites Vizzini & Mazzola 2004;Papadimitriou et al, 2005;Vizzini et al, 2005;Tomas et al, 2006;Pérez et al, 2008;Lassauque et al, 2010). The intermediate values measured in the present study confirmed a moderate anthropic effect already detected in suspended and sedimentary organic matter pools at that site (Cresson et al, 2012).…”
Section: Functioning Of Posidonia Oceanica Shoots and Influence Of Thsupporting
confidence: 75%
“…Previous results have demonstrated that several biochemical, metabolic or environmental factors affect the carbon isotopic ratio (hereafter referred as δ 13 C), such as growth rate, leaf thickness, inorganic C concentration in water, depth, light irradiance or pH (Cooper & DeNiro 1989;Lepoint et al, 2003;Fourqurean et al, 2007;Scartazza et al, 2017). Similarly, nitrogen isotopic ratio (hereafter δ 15 N) of marine primary producers is commonly used as a proxy of anthropic nitrogen releases (Costanzo et al, 2001;Vizzini & Mazzola 2004;Vizzini et al, 2005;Pérez et al, 2008;Lassauque et al, 2010;Vermeulen et al, 2011), but recent results indicated that δ 15 N could be used to track fluxes of matter within the shoot (Scartazza et al, 2017). Thus, isotopic differences between plant part types might be expected, since the physiology, metabolism and environmental context of the P. oceanica meadow change between plant-part types and seasons.…”
Section: Introductionmentioning
confidence: 99%
“…, Lassauque et al. ). Given the aforementioned reasons, P. oceanica has been identified under Community Legislation (European Council Directive 92/43/CEE, habitat code 1120; P. oceanica meadows) as a protected species, and it has been recognized as a good descriptor of environmental quality for coastal waters (European Water Framework Directive 2000/60/EC).…”
Section: Introductionmentioning
confidence: 99%
“…Posidonia oceanica effectively accumulates high levels of pollutants and is resistant to pollution, thus persisting in the vicinity of important contamination sources. Being photosynthetic species with a coastal distribution, seagrasses are mainly susceptible to a reduction in water quality and light availability linked to both natural and anthropogenic factors (Ruiz and Romero 2001, P erez et al 2008, Lassauque et al 2010. Given the aforementioned reasons, P. oceanica has been identified under Community Legislation (European Council Directive 92/43/CEE, habitat code 1120; P. oceanica meadows) as a protected species, and it has been recognized as a good descriptor of environmental quality for coastal waters (European Water Framework Directive 2000/60/EC).…”
Section: Introductionmentioning
confidence: 99%